Innovation of KAU DATANG on Fish Quarantine Center Quality Control and Safety of Fishery Products Semarang City - Gomgom Adisahputra Saragih; Retno Sunu Astuti; Budi Puspo Priyadi; Teuku Afrizal (Universitas Medan Area, 2022)
The COVID-19 pandemic has resulted in demands for the provision of public services by minimizing face-to-face services. BKIPM Semarang in its efforts to provide good public services to the community continues to strive for innovation. One of the innovations created by BKIPM is the KAU DARANG (Fish Quarantine is for You Now) innovation. This innovation is a public service innovation where people can get a certificate of fishery quality in physical form without having to come to the BKIPM Semarang office because the certificate will be sent to their respective homes even for people whose homes are difficult to reach. The purpose of writing this article is to analyze how the process of the innovation is because the innovation is new and has never been studied before. The research method used in this study is a descriptive qualitative method with library research data collection techniques. The results of the study indicate that this innovation is a process innovation that is reinforcing or reinforcing in nature, which seeks to improve previous innovations because previous innovations only facilitated the delivery of certificates to producers which only covered certain areas. With this innovation, people do not need to crowd at UPT BKIPM Semarang to get a certificate according to their needs, but only need to submit an application online for processing and then wait for the certificate to come to their house.